2020
DOI: 10.2147/ijgm.s273056
|View full text |Cite
|
Sign up to set email alerts
|

<p>Dynamic Changes of Blood Lipids in Breast Cancer Patients After (Neo)adjuvant Chemotherapy: A Retrospective Observational Study</p>

Abstract: Background: Previous studies indicated that the (neo)adjuvant chemotherapy for breast cancer can cause significant dyslipidemia in patients, but how long this abnormality can persist is unclear so far. The purpose of this study is to investigate whether (neo)adjuvant chemotherapy has a long-term effect on blood lipids in breast cancer patients. Methods: A total of 159 newly diagnosed female breast cancer patients receiving the (neo) adjuvant chemotherapy subsequently and 159 female healthy controls were enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Breast cancer is a common cancer in women (Liu Y. et al, 2020;Wan et al, 2020). Although the diagnosis strategies like the mammogram, have been developed in recent years, the mortality rate of breast cancer is still high (Ranjkesh et al, 2020;Xu et al, 2020). As a result, innovative alternatives are needed to improve the therapeutic outcome of patients with breast cancer Studies have shown that ALT changes the cell morphology and decreases the cell viability of MDA-MB-231 and MCF-7 breast cancer cells (Liu J. et al, 2018;Cui et al, 2018).…”
Section: Breast Cancermentioning
confidence: 99%
“…Breast cancer is a common cancer in women (Liu Y. et al, 2020;Wan et al, 2020). Although the diagnosis strategies like the mammogram, have been developed in recent years, the mortality rate of breast cancer is still high (Ranjkesh et al, 2020;Xu et al, 2020). As a result, innovative alternatives are needed to improve the therapeutic outcome of patients with breast cancer Studies have shown that ALT changes the cell morphology and decreases the cell viability of MDA-MB-231 and MCF-7 breast cancer cells (Liu J. et al, 2018;Cui et al, 2018).…”
Section: Breast Cancermentioning
confidence: 99%
“…The observed disturbances may result from the influence of cytostatics on the expression of enzymes involved in lipid metabolisms such as lipoprotein lipase and lecithin cholesterol acyltransferase. Dyslipidemia is an unfavorable prognostic factor [74,75], since it leads to the development of cardiovascular disease, which is the leading cause of death in people recovering from breast cancer [23]. Our study revealed that ONS maintains a constant triglyceride level and HDL cholesterol in women with normal initial adipose tissue content during chemotherapy.…”
Section: Discussionmentioning
confidence: 60%
“…These changes are associated with poor clinical outcomes, including lower disease-free and progression-free survival and higher overall mortality [18][19][20][21]. The immediate rise in total cholesterol, LDL cholesterol, and triglycerides levels during chemotherapy in patients with breast cancer has almost become an indisputable fact [12,22,23]. Recent studies have indicated that dyslipidemia does not diminish rapidly after chemotherapy [23].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations